Revealing Rembrandt - Parker, Andrew J. (Frontiers in Neuroscience, 2014)
The power and significance of artwork in shaping human cognition is self-evident. The starting point for our empirical investigations is the view that the task of neuroscience is to integrate itself with other forms of knowledge, rather than to seek to supplant them. In our recent work, we examined a particular aspect of the appreciation of artwork using present-day functional magnetic resonance imaging (fMRI). Our results emphasised the continuity between viewing artwork and other human cognitive activities. We also showed that appreciation of a particular aspect of artwork, namely authenticity, depends upon the co-ordinated activity between the brain regions involved in multiple decision making and those responsible for processing visual information. The findings about brain function probably have no specific consequences for understanding how people respond to the art of Rembrandt in comparison with their response to other artworks. However, the use of images of Rembrandt’s portraits, his most intimate and personal works, clearly had a significant impact upon our viewers, even though they have been spatially confined to the interior of an MRI scanner at the time of viewing. Neuroscientific studies of humans viewing artwork have the capacity to reveal the diversity of human cognitive responses that may be induced by external advice or context as people view artwork in a variety of frameworks and settings.